Histological pattern of focal segmental glomerulosclerosis and its clinical correlation - Wani, Asif Sadiq; Zahir, Zafirah (International Journal of Research in Medical Sciences, 2022)
Background: Focal segmental glomerulosclerosis (FSGS) is a pattern of injury and it has five histological subtypes with varying prognosis and therapeutic response. Our aim was to study the pattern of primary FSGS in our population along with their clinicopathological characteristics. Methods: This is a 2-year retrospective, single centre cohort, observational study. All adult patients with primary FSGS were identified. Results: There were 51 patients of primary FSGS. The mean age of patients was 37.2±15.3 years with overall male dominance. The clinical presentations were nephrotic syndrome (88.2%), proteinuria with hematuria (11.7%), hypertension (47.05%) and renal insufficiency (60%). FSGS-NOS were seen in 26 patients, tip variant in 11, perihilar in 6, cellular variant in 6 and collapsing variant in 2 patients. The mean age of collapsing variant was significantly less than others (20.5±9.1 years vs 37.2±15.3 years). Massive proteinuria was seen in collapsing and tip variant significantly higher than rest of the variants and tip variant had the least degree of interstitial fibrosis and tubular atrophy. Conclusions: FSGS is a pattern of injury which shows histological variations. Although it most commonly affects males, tip and cellular variants show female preponderance. Massive proteinuria was mostly seen in collapsing and tip variants and the features of chronicity were mostly seen in tip variant. Larger studies are required for the differences in treatment protocols and prognosis of different variants.